Preparation method of nanocomposite biomaterial and application thereof

CN116870233BActive Publication Date: 2026-10-23田卫群
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211407281.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-10
Publication Date
2026-10-23
Estimated Expiration
2042-11-10

AI Technical Summary

Technical Problem

其产品的优点是有良好的抗菌和抗炎性能、良好的生物相容性、优良的生物可降解性、可促进组织和细胞的生长等优点,缺点是机械强度差、会引起免疫反应等

Benefits of technology

[0014]本发明通过静电纺丝纺制纳米复合生物材料,该纳米复合生物材料生物相容性好,并且可以使PRP(富血小板血浆)缓释血小板源性生长因子(PDGF)、血管内皮生长因子(VEGF)、转化生长因子(TGF-β)生长因子,皮下注射PRP(富血小板血浆)+纳米复合生物材料,伤口修复良好。并且本发明中的原料中选用鱼皮胶原,不易引起免疫原性反应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116870233B_ABST
    Figure CN116870233B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a nanocomposite biomaterial, which comprises the following steps: purifying HNTs, adding water to obtain an HNTs aqueous solution, adding sodium metaphosphate into the HNTs aqueous solution, dissolving fish skin collagen in a mixed solution of a 98% mass fraction formic acid solution and anhydrous ethanol, then adding the HNTs dispersed by sodium metaphosphate, stirring magnetically at room temperature, placing into an EP tube, ultrasonic oscillation for 25 min, electrospinning to obtain a nanocomposite biomembrane material, freezing and drying in a vacuum freeze dryer at-50 DEG C, sterilizing by 15kGy of cobalt-60 irradiation, and obtaining the nanocomposite biomaterial. The nanocomposite biomaterial is prepared by electrospinning, has good biocompatibility, can activate platelet-rich plasma (PRP) separated and prepared by a PRP tube and release growth factors, and promotes good wound healing and repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of regenerative medicine technology, specifically relating to a method for preparing nanocomposite biomaterials and their applications. Background Technology

[0002] Currently, many dressing products are available for treating acute and chronic wound repair. Commercial dressing products can be broadly divided into three categories: The first category consists of traditional dressing products, such as gauze and bandages, which simply cover the wound. Their advantages are ease of use and low price. Disadvantages include dryness, inability to maintain a moist wound repair microenvironment, and difficulty in removal once adhered to the wound, potentially causing secondary damage during replacement. The second category comprises modern dressing products, which offer better biocompatibility and moisture retention than traditional dressings. These dressings are made from synthetic polymers, such as polyurethane, glycerol-based polymers, and cross-linked polymers synthesized from carbohydrates. Their product forms include films, foams, and hydrogels. The advantages of these materials include transparency allowing observation of wound changes, forming a bacterial barrier, excellent permeability to gases and water vapor, ease of replacement and comfortable use, high moisture retention to maintain a moist wound microenvironment, and non-toxic, rapid hemostasis. The disadvantages include weak adhesion to wounds, limited adsorption capacity, making it unsuitable for wounds with high exudate, and poor biodegradability. The third category is bioactive dressings. These dressings are made from biopolymers, including gelatin, collagen, chitosan, and silk protein. Their forms include foam, sponge, film, hydrogel, and nanofiber membranes. Bioactive substances such as antibacterial drugs, growth factors, and nanoparticles are added to these biopolymers to create bioactive dressings. The advantages of these products include good antibacterial and anti-inflammatory properties, good biocompatibility, excellent biodegradability, and the ability to promote tissue and cell growth. The disadvantages include poor mechanical strength and the potential to trigger immune responses. Summary of the Invention

[0003] The technical problem to be solved by this invention is to provide a method for preparing nanocomposite biomaterials and their applications, addressing the shortcomings of the prior art. This method involves electrospinning nanocomposite biomaterials, which exhibit good biocompatibility and can enable the sustained release of platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), and transforming growth factor (TGF-β) from platelet-rich plasma (PRP). Subcutaneous injection of PRP + nanocomposite biomaterials (nanocollagen fibers and HNTs) results in good wound repair.

[0004] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a method for preparing nanocomposite biomaterials, the method being as follows:

[0005] S1. After purifying HNTs, add water to obtain an aqueous solution of HNTs. Add sodium hexametaphosphate to the aqueous solution of HNTs to obtain HNTs dispersed with sodium hexametaphosphate. The mass fraction of the aqueous solution of HNTs is 0.1-10%.

[0006] Fish skin collagen was dissolved in a mixture of 98% formic acid solution and anhydrous ethanol, and then HNTs dispersed with sodium hexametaphosphate were added. The mixture was magnetically stirred at room temperature for 4 hours to obtain the electrospinning solution of the nanocomposite material.

[0007] Halloysite nanotubes (HNTs) can improve the mechanical properties, drug loading capacity, cell adsorption, and hemostatic properties of polymers. HNTs are natural inorganic nanomaterials with the chemical formula Al₂Si₂O₅(OH)₄·nH₂O. HNTs have a length of (0.2-1.5) μm, an inner diameter of (10-40) nm, an outer diameter of (40-70) nm, and an aspect ratio (L / D) of (10-50). The hollow cavity microstructure and porosity of HNTs enable them to have excellent loading and adsorption capabilities for active substances.

[0008] S2. The electrospinning solution of the nanocomposite material obtained in S1 is placed into an EP tube and ultrasonically vibrated for 25 min. The vibrated electrospinning solution of the nanocomposite material is extracted with a syringe. The needle of the syringe is connected to the connector of the electrospinning instrument. The parameters of the electrospinning instrument are set as follows: distance 20 cm, voltage 24 kV to 26 kV, pump speed 0.3 mL / h, receiver rotation speed 200 rpm, temperature 18℃ to 22℃, humidity 30% to 50%. Electrospinning is performed. After electrospinning for 8 to 10 h, a nanofiber membrane is obtained. The membrane is freeze-dried in a vacuum freeze dryer at -50℃ for 48 h and sterilized by irradiation with 15 KGy of cobalt-60 for 4 h to obtain the nanocomposite fiber membrane biomaterial.

[0009] Preferably, the mass ratio of sodium hexametaphosphate to the HNTs aqueous solution in S1 is 1:200;

[0010] The electrospinning solution of the nanocomposite material contains 98% formic acid solution, anhydrous ethanol, HNTs dispersed with sodium hexametaphosphate, and fish skin collagen in a ratio of (2-3) mL: (1-1.5) mL: 0.02 g: (0.35-0.48) g.

[0011] This invention also provides the application of the nanocomposite biomaterial prepared above, wherein the nanocomposite biomaterial is used to activate platelet-rich plasma (PRP), and after the platelet-rich plasma is activated by the nanocomposite biomaterial, HNTs therein have a sustained-release effect on growth factors.

[0012] The present invention also provides the application of the nanocomposite biomaterial prepared above, wherein the nanocomposite biomaterial is used to prepare materials for wound repair.

[0013] Compared with the prior art, the present invention has the following advantages:

[0014] This invention utilizes electrospinning to fabricate nanocomposite biomaterials. These nanocomposite biomaterials exhibit good biocompatibility and enable the sustained release of platelet-rich plasma (PRP), platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), and transforming growth factor-β (TGF-β). Subcutaneous injection of PRP combined with the nanocomposite biomaterials results in excellent wound healing. Furthermore, the raw material used in this invention is fish skin collagen, which is less likely to induce immunogenic reactions.

[0015] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments. Attached Figure Description

[0016] Figure 1 The nanocomposite biomaterial of Example 1 of this invention is in the range of (600-3800) cm. -1 Fourier infrared spectrum.

[0017] Figure 2 These are an appearance image of the fish skin collagen electrospinning solution and a scanning electron microscope image of the nano-collagen membrane used in the preparation of the control nano-collagen membrane in Example 1 of this invention. Figure 3 This is a diameter distribution diagram of nanofibers in the control nanocollagen membrane in Example 1 of the present invention.

[0018] Figure 4 These are the appearance diagram of the electrospinning solution of the nanocomposite material in Example 1 of the present invention and the scanning electron microscope image of the nanocomposite biomaterial in step S2.

[0019] Figure 5 This is a diameter distribution diagram of the nanofibers in the nanocomposite biomaterial in Example 1.

[0020] Figure 6 This is a trend chart showing the experimental effect of nanocomposite biomaterials activating platelet-rich plasma to release platelet-derived growth factor (PDGF) in Example 1.

[0021] Figure 7 This is a graph showing the experimental results of CCK-8 in Example 1.

[0022] Figure 8 This is a diagram showing the results of skin repair in SD rats in Example 1.

[0023] Figure 9 This is a bar graph showing the wound area healing rate of SD rat skin repair in Example 1. Detailed Implementation

[0024] Example 1

[0025] The method for preparing the nanocomposite biomaterial in this embodiment is as follows:

[0026] S1. After purifying HNTs (haloite nanotubes), add water to obtain an HNTs aqueous solution with a mass fraction of 10%. Add sodium hexametaphosphate to the HNTs aqueous solution to obtain HNTs dispersed with sodium hexametaphosphate. The mass ratio of sodium hexametaphosphate to the HNTs aqueous solution is 1:200.

[0027] 0.48 g of fish skin collagen was dissolved in a mixture of 98% formic acid solution (3 mL) and anhydrous ethanol (1 mL), and then 0.02 g of HNTs dispersed in sodium hexametaphosphate was added. The mixture was magnetically stirred at room temperature for 4 h to obtain the electrospinning solution of the nanocomposite material.

[0028] In this embodiment, sodium hexametaphosphate is added to the HNTs aqueous solution, which enables the HNTs to be suspended and dispersed in the electrospinning solution;

[0029] S2. Pour the electrospinning solution of the nanocomposite material obtained in S1 into an EP tube and sonicate for 25 min. Draw out the oscillated electrospinning solution of the nanocomposite material with a syringe. Connect the needle of the syringe to the connector of the electrospinning instrument (22G electrospinning needle). Then fix the syringe on the micro-infusion pump, turn on the DC high voltage power supply, and set the parameters of the electrospinning instrument as follows: distance 20 cm, voltage 24 kV, pump speed 0.3 mL / h, receiver rotation speed 200 rpm, temperature 18℃, humidity 30%. Perform electrospinning. After electrospinning for 8 h, obtain a nanofiber membrane. Freeze-dry in a vacuum freeze dryer at -50℃ for 48 h, and sterilize with 15 KGy cobalt-60 irradiation for 4 h to obtain nanocomposite biomaterial.

[0030] In this embodiment, a nanofiber membrane is used as a control. The preparation method of the nanocollagen membrane is as follows:

[0031] 3 mL of 98% formic acid solution and 1 mL of anhydrous ethanol were mixed evenly, and 0.48 g of fish skin collagen was added. The mixture was magnetically stirred for 4 h at room temperature to obtain a fish skin collagen electrospinning solution. The solution was poured into a 5 mL EP tube and ultrasonically vibrated for 25 min. Then, the solution was drawn up with a 20 mL syringe and vibrated. An electrospinning needle (a 22 G electrospinning needle) was attached to the connector. The syringe was then fixed to a micro-infusion pump and the DC high-voltage power supply was turned on. The parameters of the electrospinning instrument were set as follows: distance 20 cm, voltage 22-25 kV, pump speed 0.3 mL / h, receiver rotation speed 200 rpm. Electrospinning was performed to obtain a nanofilm. The nanofilm was freeze-dried in a vacuum freeze dryer at -50 °C for 48 h and sterilized by irradiation with 15 KGy cobalt-60 for 4 h to obtain a nanocollagen membrane.

[0032] Figure 1 HNTs, nanocollagen membranes (control), and the nanocomposite biomaterials prepared in this example were compared at (600-3800) cm⁻¹. -1 The Fourier transform infrared (FTIR) spectra are shown in the figure. Curve C represents the FTIR spectrum of the nanocomposite biomaterial, curve collagen represents the FTIR spectrum of the nanocollagen membrane (control), and curve HNT represents the FTIR spectrum of halloysite nanotubes. For the nanocomposite biomaterial prepared in this embodiment, the FTIR spectrum is 3305 cm⁻¹. -1 2900cm -1 1640cm -1 1540cm -1 There are four characteristic peaks, corresponding to the stretching vibration peak of free NH, the stretching vibration peak of CH, the C=O stretching vibration (amide I band), the NH bending vibration, and the CN stretching vibration peak (amide II band). These are generally located at (3400-3440) cm⁻¹. -1 The peak of the free NH stretching vibration is located at (1550-1600) cm⁻¹. -1 The peak at 1040 cm⁻¹ is amide II, but in the nanocomposite biomaterial prepared in this embodiment, both characteristic peaks shift to lower wavenumbers, indicating that hydrogen bonds are formed between the nanocollagen fibers and HNTs in the nanocomposite biomaterial, and hydrogen bonds are formed between the amino groups of the nanocollagen fibers and the Si-O bonds or hydroxyl groups of the HNTs. Furthermore, the nanocomposite biomaterial shows a peak at 1040 cm⁻¹. -1 and 910cm -1 There are two characteristic peaks, which correspond to the Si-O-Si stretching vibration peak of HNTs and the Al-O stretching vibration peak of the inner surface of HNTs.

[0033] Observation of nano-collagen membranes by SEM Figure 2 ) and the nanocomposite biomaterials prepared in this embodiment ( Figure 4 ) surface morphology. Figure 2The left side shows the appearance of the fish skin collagen electrospinning solution, and the right side shows a scanning electron microscope image of the nano-collagen membrane.

[0034] Figure 4 The left side shows the appearance of the electrospinning solution for the nanocomposite material in step S1, and the right side shows a scanning electron microscope image of the nanocomposite biomaterial. The images clearly show that the surface of the nanocollagen fibers is smooth, and the fiber diameter distribution is relatively uniform, with an average diameter of 208.2 nm. Figure 3 Compared to nano-collagen fibers, the incorporation of HNTs did not significantly alter the surface morphology of the nano-collagen fibers; only the diameter of the nano-collagen fibers increased, with an average diameter of 235.6 nm. Figure 5 The main reason is that adding negatively charged HNTs to the collagen electrospinning solution reduces the charge density on the spinneret surface, which in turn increases the diameter of the resulting fibers.

[0035] This embodiment also provides the application of the nanocomposite biomaterial prepared above. The nanocomposite biomaterial is used to activate platelet-rich plasma (PRP). After the platelet-rich plasma is activated by the nanocomposite biomaterial, the HNTs in it have a sustained-release effect on growth factors such as platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), and transforming growth factor (TGF-β).

[0036] In this embodiment, platelet-rich plasma (PRP) can be prepared using PRP tubes. The PRP tubes can be made of glass or plastic and are pre-vacuumed. From bottom to top, the PRP tubes contain PRP separating gel and anticoagulant. These PRP tubes are provided by Zhuhai Langtai Biotechnology Co., Ltd. Each tube contains 3 grams of separating gel and 1 ml of anticoagulant, and is pre-vacuumed, allowing for the extraction of (8-10) ml of whole blood per tube.

[0037] PRP separating gel is a bio-inert polymeric chemical with certain thixotropic properties and specific gravity, ranging from 1.05 to 1.06.

[0038] The anticoagulant is a (0.1-0.121) mol / L sodium citrate solution. 1 mL of anticoagulant can anticoagulate 8 mL to 10 mL of whole blood.

[0039] The average platelet concentration in PRP in this experiment was 600 × 10⁻⁶. 9 / L. (Four volunteers were selected, and PRP was prepared using PRP tubes according to the operating instructions of Zhuhai Langtai Biotechnology Co., Ltd. The average platelet concentration in the PRP was 600 × 10⁻⁶.) 9 / L. )

[0040] In this embodiment, experiments were conducted to activate PRP using bovine thrombin, nanocollagen (control), and the nanocomposite biomaterial prepared in this embodiment, and the release curves of platelet-derived growth factor (PDGF) and other substances over time were detected. Figure 6 As shown in the figure, when PRP is activated with bovine thrombin, the concentration of platelet-derived growth factor (PDGF) reaches its highest value of 40,600 pg / mL 2 hours after activation. Subsequently, the concentration of PDGF gradually decreases with increasing time. This is mainly because after PRP is activated by bovine thrombin, the growth factor is released explosively and is released completely within 2 hours. As time increases, the growth factor will slowly degrade.

[0041] When PRP is activated using a nano-collagen membrane, the concentration of PDGF gradually increases over time, demonstrating that the nano-collagen membrane can slowly release growth factors from PRP, and the amount released is greater than the amount degraded.

[0042] The release pattern of PRP activated using a nanocomposite material is similar to that of the nanocollagen membrane, but the concentration of growth factors after day 5 is significantly higher. This demonstrates that the composite material not only enables PRP to release growth factors slowly but also allows for a more complete release of growth factors from platelets. This is because HNTs are uniformly distributed within the nanomembrane. On one hand, the hollow and porous nanotube structure of HNTs allows them to adsorb the released PDGF, thus achieving more effective control over the slow release process. On the other hand, HNTs can activate platelets, enabling PRP to release PDGF more completely and in greater quantities. The PDGF concentration on day 14 was 36,000 pg / mL, comparable to the concentration (40,600 pg / mL) within 2 hours of activation with bovine thrombin.

[0043] The experiment in this embodiment on the activation of PRP by the nanocomposite biomaterial also showed that it could release vascular endothelial growth factor (VEGF) and transforming growth factor (TGF-β). The experimental results showed that the concentration of VEGF in plasma increased over time, showing a fluctuating phenomenon, but the overall trend was upward. The concentration of TGF-β in plasma gradually increased over time, indicating that the nanocomposite biomaterial activated the secretion of platelet-rich plasma (PRP) and had a sustained-release effect on the release of VEGF and TGF-β growth factors.

[0044] This embodiment also provides an application of the nanocomposite biomaterial prepared above. The nanocomposite biomaterial prepared in this embodiment is used to prepare materials for wound healing and repair.

[0045] This embodiment also included a CCK-8 experiment:

[0046] Experimental procedure:

[0047] CCK-8 reagent contains WST-8, a compound similar to MTT. In the presence of the electron-coupling reagent 1-MethoxyPMS, it can be reduced by mitochondrial dehydrogenases to the highly water-soluble formazan product, Formazan. The amount of Formazan produced is directly proportional to the number of viable cells. Therefore, this characteristic can be used for cell proliferation and cytotoxicity detection analysis; the faster and more abundant the cell proliferation, the darker the color; the lighter the color, the greater the cytotoxicity. The specific operation is as follows:

[0048] (1) Take healthy L929 cells and wash them three times with PBS. After resuspending the adherent cells with trypsin and centrifuging, remove the supernatant and resuspend the cell pellet in DMEM + 10% FBS cell culture medium to a concentration of 1×10⁻⁶. 4 Cells / mL were seeded into 96-well plates at a rate of 100 μL of cell suspension per well, with 5 wells per experimental group. An equal volume of cell suspension was added to the remaining wells as a negative control group. After gently shaking the 96-well plate to ensure even seeding, the cells were transferred to a CO2 cell culture incubator and cultured for 24 hours.

[0049] (2) Preparation of the extract. The composite nanomembrane was added to 10 times its volume of 0.9% NaCl solution (or cell culture medium) at a ratio of 1:10 to prepare a standard extract (extracted for 24 hours, centrifuged, and the supernatant collected). Concentration gradients were set at dilution factors of 75%, 50%, 25%, and 12.5%.

[0050] (3) After removing the 96-well plate, place it on a clean bench and remove the culture medium from the 96-well cell culture plate with a pipette. Then wash each well three times with sterile PBS solution. Add the previously prepared gradient extraction solutions of various concentrations to the wells inoculated with cells, adding 200 μL of solution to each well. Add 200 μL of complete culture medium to the wells of the negative control group. Cover the 96-well culture plate, spray with alcohol, and return it to the carbon dioxide incubator for incubation. After incubation for 24 h, 48 h, and 72 h, add CCK-8 solution at a concentration of 10% and continue incubation for 1 h. Measure the absorbance of each culture well at 450 nm.

[0051] Experimental results:

[0052] like Figure 7As shown in the CCK-8 assay, the relative proliferation activity of L929 cells was significantly higher than that of the negative control group at all extract concentrations (P < 0.05). Notably, the nanocomposite material group reached its peak at 48 h, at which point L929 cells exhibited the strongest viability. The OD value decreased after 72 h, indicating that high-concentration extracts could mildly inhibit cell proliferation. Therefore, the composite membrane not only lacks toxicity to L929 cells but also promotes their proliferation.

[0053] This embodiment also included a skin repair experiment on SD rats:

[0054] The experimental procedure is as follows:

[0055] (1) Thirty-two SPF-grade 8-week-old male SD rats, weighing 200g±20g, were selected. Before the experiment, the rats were housed in IVC cages for one week for acclimatization. Using a randomization method, 27 rats were randomly divided into 3 groups of 9 rats each: saline (NS) group, PRP+nanocollagen membrane group, and PRP+nanocomposite biomaterial group. There were no statistically significant differences among the groups.

[0056] (2) Blood was drawn from the heart of the remaining 5 rats. After successful anesthesia, the chest hair of each rat was shaved and routinely disinfected. Using a syringe pre-filled with 0.3 mL sodium citrate solution, 10 mL of venous whole blood was drawn into the right ventricle, for a total of 20 mL. The blood was then centrifuged in a 5 mL centrifuge tube. The tube was first centrifuged at 800 g for 10 min, and all the supernatant and the liquid 3 mm below the interface were collected and transferred to another centrifuge tube for a second centrifuge at 1000 g for 10 min. The upper 3 / 4 of the liquid was discarded, and the remaining 3 mL was shaken well to obtain PRP, for a total of 15 mL of PRP.

[0057] (3) Twenty-seven rats were anesthetized (using a small animal anesthesia machine, isoflurane anesthesia, oxygen flow rate of 0.8 L / min, 5% isoflurane induction, and 1.5%-2% maintenance). After successful anesthesia, the rats were placed in a prone position with their limbs spread out, exposing their backs. The hair on the back was shaved off, and the hair was washed with warm sterile saline. A circle with a diameter of 1.5 cm was drawn on the skin on both sides of the spine on the left side of the spine, and two circles with a diameter of 1.5 cm were drawn on the right side. The skin was then disinfected with povidone-iodine, and a sterile surgical drape was applied. The skin and subcutaneous fat on the back were cut off along the markings with sterile surgical scissors to expose the surface of the muscle layer. If there was bleeding, the skin was wiped with sterile gauze soaked in sterile saline and the bleeding was gently stopped by pressing.

[0058] (4) Treatment of skin lesions in SD rats: ① PRP + nano-collagen group, ② PRP + nanocomposite biomaterial group, respectively, with 2*2*2mm 3The nano-collagen membrane and nanocomposite biomaterial membrane were placed in 0.5 mL of PRP and incubated at 37°C for 2 hours. After 2 hours, the membrane dissolved. The mixture was then injected evenly onto the wound surface, covered with a sterile surgical dressing, and then covered with Vaseline gauze and sterile gauze. The adhesive tape was firmly attached, and the wound healing was observed three days later. ③ Saline group (NS group): 0.5 mL of saline was injected evenly onto the wound surface, covered with a sterile surgical dressing, and then covered with Vaseline gauze and sterile gauze. The adhesive tape was firmly attached, and the wound healing was observed three days later. Observation indicators: Photos were taken on days 7, 14, and 21 after modeling, and the healing rate was calculated. Newly formed tissue and 3 mm of normal tissue at the edge of the wound up to the subcutaneous fat layer were taken, fixed overnight with 4% paraformaldehyde at 4°C, and stained with HE for examination.

[0059] Calculate the healing rate using the following formula:

[0060] Healing rate (%) = [(A0 - At) / A0] × 100%

[0061] In the formula, A0 is the original wound area; At is the unhealed wound area.

[0062] Experimental results:

[0063] like Figure 8 As shown, compared with the NS group, the wound healing rates of both the PRP + nanocollagen membrane group and the PRP + nanocomposite biomaterial group were significantly higher than those of the NS group (P < 0.01). The healing rate of the PRP + nanocollagen group also showed a statistically significant difference compared with the PRP + nanocollagen group (P < 0.05), demonstrating that both the PRP + nanocollagen group and the PRP + nanocomposite biomaterial group promoted wound repair, but the repair effect of the PRP + nanocomposite biomaterial group was more pronounced. After mixing with the composite nanobiomaterial, the HNTs in the composite nanobiomaterial were uniformly distributed in the nanomembrane. On the one hand, the nanocollagen membrane provided a good network and biological scaffold function, expanding the space for material exchange and metabolism between tissues, as well as the contact area with the nanocollagen. On the other hand, due to their hollow and porous nanotube structure, HNTs can adsorb released PDGF, thus achieving more effective control over the slow release process. Furthermore, HNTs can activate platelets, causing their PRPs to release PDGF more thoroughly and in greater quantities, thereby better promoting the proliferation and migration of epithelial cells and thus promoting wound healing. The wound area healing rate is shown in Table 1, and the bar chart is shown below. Figure 9 As shown.

[0064] Table 1. Percentage of wound area healing rate (%) (n=3); )

[0065] PRP + Nano Collagen Group 0 51.90±0.10 73.83±0.01 76.95±0.00 PRP+ nanocomposite biomaterials 0 70.09±0.12 80.62±0.02 88.51±0.01 NS Group 0 22.57±0.11 50.72±0.04 69.68±0.06

[0066] Example 2

[0067] The method for preparing the nanocomposite biomaterial in this embodiment is as follows:

[0068] S1. After purifying HNTs, add water to obtain an aqueous solution of HNTs with a mass fraction of 0.1%. Add sodium hexametaphosphate to the aqueous solution of HNTs to obtain HNTs dispersed with sodium hexametaphosphate. The mass ratio of sodium hexametaphosphate to the aqueous solution of HNTs is 1:200.

[0069] 0.35g of fish skin collagen was dissolved in a mixture of 98% formic acid solution (2mL) and anhydrous ethanol (1.5mL), and then 0.02g of HNTs dispersed in sodium hexametaphosphate was added. The mixture was magnetically stirred at room temperature for 4h to obtain the electrospinning solution of the nanocomposite material.

[0070] In this embodiment, sodium hexametaphosphate is added to HNTs, which enables HNTs to be suspended and dispersed in the electrospinning solution;

[0071] S2. Pour the electrospinning solution of the nanocomposite material obtained in S1 into an EP tube and sonicate for 25 min. Use a syringe to extract the oscillated electrospinning solution of the nanocomposite material. Connect the needle of the syringe to the connector of the electrospinning instrument (22G electrospinning needle). Then fix the syringe on the micro-infusion pump, turn on the DC high voltage power supply, and set the parameters of the electrospinning instrument as follows: distance 20 cm, voltage 26 kV, pump speed 0.3 mL / h, receiver rotation speed 200 rpm, temperature 22℃, humidity 50%. Perform electrospinning. After electrospinning for 10 h, obtain a nanofiber membrane. Freeze-dry in a vacuum freeze dryer at -50℃ for 48 h, and sterilize with 15 KGy cobalt-60 irradiation for 4 h to obtain the nanocomposite biofilm material.

[0072] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a nanocomposite biomaterial, characterized in that, The method is as follows: S1. After purifying HNTs, water is added to obtain an aqueous solution of HNTs. Sodium hexametaphosphate is then added to the aqueous solution of HNTs to obtain HNTs dispersed in sodium hexametaphosphate. The mass fraction of the aqueous solution of HNTs is 0.1-10%. Fish skin collagen was dissolved in a mixture of 98% formic acid solution and anhydrous ethanol, and then HNTs dispersed with sodium hexametaphosphate were added. The mixture was magnetically stirred at room temperature for 4 hours to obtain the electrospinning solution of the nanocomposite material. The mass ratio of sodium hexametaphosphate and HNTs aqueous solution in S1 is 1:200; The electrospinning solution of the nanocomposite material contains 98% formic acid solution, anhydrous ethanol, HNTs dispersed in sodium hexametaphosphate, and fish skin collagen in a ratio of (2-3) mL: (1-1.5) mL: 0.02 g: (0.35-0.48) g. S2. The electrospinning solution of the nanocomposite material obtained in S1 is placed into an EP tube and ultrasonically vibrated for 25 min. The vibrated electrospinning solution of the nanocomposite material is drawn out with a syringe. The needle of the syringe is connected to the connector of the electrospinning instrument. The parameters of the electrospinning instrument are set as follows: distance 20 cm, voltage 24 kV to 26 kV, pump speed 0.3 mL / h, receiver rotation speed 200 rpm, temperature 18℃ to 22℃, humidity 30% to 50%. Electrospinning is performed. After electrospinning for 8 to 10 h, a nanofiber membrane is obtained. The membrane is freeze-dried in a vacuum freeze dryer at -50℃ for 48 h and sterilized by irradiation with 15 KGy of cobalt-60 for 4 h to obtain a nanocomposite fiber membrane biomaterial. The nanocomposite biomaterial is used to activate platelet-rich plasma and release growth factors. The nanocomposite biomaterial is used to prepare materials for wound healing and repair.